2015
DOI: 10.3758/s13414-015-0955-9
|View full text |Cite
|
Sign up to set email alerts
|

With peppermints you’re not my prince: Aroma modulates self-other integration

Abstract: Recent studies showed that self-other integration, as indexed by the joint Simon effect (JSE), can be modulated by biasing participants towards particular (integrative vs. exclusive) cognitive-control states. Interestingly, there is evidence suggesting that such control states can be induced by particular odors: stimulating odors (e.g., peppermint aroma) seem to induce a more focused, exclusive state; relaxing odors (e.g., lavender aroma) are thought to induce a broader, more integrative state. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Compared to control conditions (peppermint odor, no scent), the natural aroma of lavender increased the amount of money participants gave to a trustee (Sellaro et al, 2015b), a sign of trust. In another study, lavender odor was found to increased self-other integration (Sellaro et al, 2015a), which may help bridge perspectives between individuals and facilitate trust. Even outside of the lab, certain scents (e.g., orange odor) facilitated approach-related interpersonal behavior (e.g., dancing, drinking; Schifferstein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to control conditions (peppermint odor, no scent), the natural aroma of lavender increased the amount of money participants gave to a trustee (Sellaro et al, 2015b), a sign of trust. In another study, lavender odor was found to increased self-other integration (Sellaro et al, 2015a), which may help bridge perspectives between individuals and facilitate trust. Even outside of the lab, certain scents (e.g., orange odor) facilitated approach-related interpersonal behavior (e.g., dancing, drinking; Schifferstein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When noticed, hexanal has the pleasant smell of freshly cut grass (Duke, 2015), but more often, hexanal remains “hidden” in mixtures that subserve some communication function. Indeed, gas chromatography-mass spectrometry (GC-MS) has revealed the presence of hexanal in body odor samples (Jha and Hayashi, 2017), human skin emanations (Pandey and Kim, 2011), where it may serve a social communication function, but also in lavender (ter Heide et al, 1970; Khan and Abourashed, 2010), a smell that was shown to enhance trust in humans (Sellaro et al, 2015a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that aroma inhalation of essential oils exhibits various positive psychophysiological effects by regulating the central nervous system function . For example, peppermint aroma enhances memory, visual attention, task performance, and alertness, and lavender aroma promotes behavior commitment and interpersonal trust …”
Section: Introductionmentioning
confidence: 99%
“…13,14 For example, peppermint aroma enhances memory, visual attention, task performance, and alertness, and lavender aroma promotes behavior commitment and interpersonal trust. 15 The influence of fragrances on brain function has been determined by using an electrophysiological technique called the electroencephalography (EEG). The EEG measures the neuronal electrical activity from electrodes located on the scalp.…”
mentioning
confidence: 99%
See 1 more Smart Citation